PREVALENCE OF GROUP B STREPTOCOCCAL INFECTION IN ANTENATAL WOMEN - UDAYA RUBINI.U; SHABANA PRAVEEN; RADHA MADHAVAN (International Journal of Pharma and Bio Sciences, 2013)
Group B streptococci (GBS) are found to colonize the vaginal skin colonisation and is a known risk factor for morbidity and mortality among newborns as well as mothers. The present study was undertaken to study the prevalence of vaginal colonization by GBS among pregnant women. This was a cross sectional study conducted in a tertiary care teaching hospital during January 2012 – February 2013. A total of 132 vaginal swabs were taken from pregnant women of third trimester. All samples were processed according to standard microbiological protocol. Antibiotic susceptibility testing was done. CAMP test and serotyping was done for confirmation of GBS. Out of 132 samples collected the culture positivity rate of GBS was 9.1%. Among the positives 54.5% were from asymptomatic cases. In conclusion,all the pregnant females should be subjected to speculum examination and screening for GBS by high vaginal swab culture